Pengaruh Repositioning terhadap Customer Loyalty melalui Brand Equity sebagai Variabel Mediasi pada Layanan Kredit Konsumtif PT. Bank Pembangunan Daerah Jambi - Febby Nanda Utami; Hamdiah; Adi Ihsan Syukri Amri; Rama Dhonal (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
Business development in banking sector has grown and progressively increase. Bank Jambi (PT. Bank Pembangunan Daerah Jambi) which is close to the image of "Bank PNS" is determined to become a professional bank, especially in consumptive credit services. The purpose of this study was to analyze the effect of repositioning on customer loyalty, analyze the effect of repositioning on brand equity, analyze the effect of brand equity on customer loyalty and analyze the effect of repositioning on customer loyalty mediated by brand equity in consumer credit services of Bank Pembangunan Daerah Jambi. The method used in this research is descriptive method through a survey approach. The sample respondents is 100 customer that using the consumptive credit services on Bank Pembangunan Daerah Jambi. The research variables are Repositioning, Customer Loyalty and Brand Equity. Data analysis was carried out with two approaches, qualitative and quantitative, with Structural Equation Modeling (SEM). The result of this research is Repositioning results have a significant effect on Customer Loyalty, Repositioning has a significant effect on Brand Equity, Brand Equity has a significant effect on Customer Loyalty and Repositioning has an indirect effect on Customer Loyalty through Brand Equity. Keywords : Repositioning, Customer Loyalty, Brand Equity, Consumer Credit Services